Understanding the value of and reasoning behind farmer adoption of carbon centric practices - Wander, Michelle M. (Burleigh Dodds Series in Agricultural Science, 2023)
Understanding how to promote farmers' use of carbon (C) centric practices known to increase soil C sequestration is needed to design information systems and orient policy, investment and environmental markets. Farmers undertake individual and collective actions using techniques that have varied over time and space according to land potential, farming systems, values and, evolving political and environmental contexts. Interviews with US Midwest conservation, conventional and organic grain farmers suggest market outlet most influences C stewardship. The number of samples needed to verify C sequestration targets by direct soil sampling is high and may temper interest in C markets; however, direct verification can reasonably be achieved by pooling data from multiple farms. Valorization-mechanisms and cooperative efforts lower costs and help individuals address large-scale issues like climate change and indirectly influence unwanted impacts of farm-size-expansion and competition for land, but do not consider benefits to family and community well-being that matter to farmers.